2021
DOI: 10.18494/sam.2021.3116
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Model Identification for Insect Electroantennogram with Printed Electrode

Abstract: The purpose of this study is to establish a method by which anyone can easily use an insect antenna as a robot olfactory sensor. Research has been conducted to use an insect antenna as a robot olfactory sensor because insect antennae are much more selective and sensitive than artificial odor sensors. To use an antenna as a robot olfactory sensor, a robot was controlled on the basis of the change in the electroantennogram (EAG) response to odor. However, EAG measurements were performed using microelectrodes or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
(27 reference statements)
0
1
0
Order By: Relevance
“…To investigate the characteristics of sensory organs, only the sensory organs can be connected to the robot, or to investigate brain functions, the robot can be operated by electrical signals from the brain. For example, to investigate the characteristics of insect sensory organs, a study has been reported in which behavioral experiments were conducted using insect antennae as sensors for a robot [42,43]. There is research that verified the validity of an antennal lobe model by using technic that use antennae as sensors for robots, reading an electroantennogram of an insect, and controlling a robot from a neuron model that represents the antennal lobe in the brain [44].…”
Section: Overview Of the Biological Experimental Setup Using Engineer...mentioning
confidence: 99%
“…To investigate the characteristics of sensory organs, only the sensory organs can be connected to the robot, or to investigate brain functions, the robot can be operated by electrical signals from the brain. For example, to investigate the characteristics of insect sensory organs, a study has been reported in which behavioral experiments were conducted using insect antennae as sensors for a robot [42,43]. There is research that verified the validity of an antennal lobe model by using technic that use antennae as sensors for robots, reading an electroantennogram of an insect, and controlling a robot from a neuron model that represents the antennal lobe in the brain [44].…”
Section: Overview Of the Biological Experimental Setup Using Engineer...mentioning
confidence: 99%